Transformation of Accounting Information Systems: An Analysis of the Impact of Digitalization on the Financial Performance of Small and Medium-Sized Enterprises in Indonesia - Andi Riska Andreani; M. Mediaty; Sri Sundari (Manunggal Halim Jaya, 2026)
Digital transformation has reshaped the financial management practices of Small and Medium-Sized Enterprises (SMEs), particularly through the adoption of digital Accounting Information Systems (AIS). In Indonesia, SMEs play a vital role in national economic growth, yet many still face challenges in adopting digital accounting technologies due to limited digital literacy, inadequate technological infrastructure, financial constraints, and resistance to change. This study aims to systematically review the impact of AIS digitalization on SME financial performance and to identify the key supporting and inhibiting factors influencing its implementation. Using a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework, this study analyzes peer-reviewed articles published between 2021 and 2026 from major academic databases, including Scopus, Web of Science, ScienceDirect, and Google Scholar. The findings indicate that AIS digitalization has a significant positive effect on SME financial performance, particularly in improving operational efficiency, financial reporting accuracy, internal control, decision-making quality, profitability, and revenue growth. The review also reveals that successful implementation is strongly influenced by human resource competence, digital literacy, management support, technological infrastructure, government support, and regulatory readiness. However, barriers such as high investment costs, limited technical skills, organizational resistance, cybersecurity risks, and inadequate infrastructure remain critical challenges. This study contributes theoretically by integrating the Resource-Based View, Technology Acceptance Model, and Technology-Organization-Environment framework to explain AIS digitalization in SMEs. Practically, the findings provide strategic insights for SMEs, technology developers, and policymakers in strengthening digital transformation and improving financial performance.